Does where you live affect how much you spend on transit? The link between urban form and household transit expenditures in Mexico City - Erick Guerra (Journal of Transport and Land Use, 2017)
Long and expensive transit trips burden millions of households in many low- and middle-income cities. Geography likely plays an important role. In Mexico City, suburban households earn 30% less than urban households, have 40% longer commutes, and spend nearly twice as much per transit trip. This paper examines the relationship between where households live in Mexico City and how much they spend on transit using a large metropolitan household travel survey matched to measures of the built environment. Transit expenditures vary systematically with neighborhood population density, land-use diversity, municipal job density, street network density, and distance to the metro and urban center. These relationships are complex and nonlinear but robust with the inclusion of household income, size, and structure. They are also relatively strong with job density, destination diversity, distance to the metro, and population density being as strongly correlated with transit expenditures as household income. In dollar values, the savings associated with more convenient household locations are substantial and in the same ballpark as total metro fare revenues and a back-of-the-envelope estimate of the total daily external costs of suburban congestion.